A study of Optimal Assignment Model Considering Quality and Worker Level in Limited-Cycle with Multiple Periods For Smart Manufacturing - Noda, Kazuma; Sun, Jing; Yamamoto, Hisashi; Dou, Run-Liang (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
In recent years, quality irregularities reported by various media have shaken public confidence in companies, impacting both sales and stock prices, even among global leaders in manufacturing. Additionally, the increase in foreign workers and variations in service length have introduced differences in worker skill levels. This study aims to identify optimal worker assignment strategies that balance quality and worker skill levels for efficient production. We propose an optimal assignment model for a smart production line in a limited-cycle, multi-period setting that considers both quality and due dates. Numerical experiments further analyze optimal arrangement strategies and characteristics across different worker skill levels.